Tomatoes and peppers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Njih Mbasho Abdou is president of a farmers? group which grows tomatoes and peppers for local markets in northern Cameroon. By careful planning they are able to earn a good price for their crops.